The Plot In The Narrative Written by The University Students - Basar Lolo Siahaan; Sanggam Siahaaan; Daniel Binsah Lumbangaol (Jurnal Ilmu Sosial dan Humaniora, 2026)
This research investigates the plot structure used in narrative texts written by fourth semester students of teacher training and education faculty of Universitas HKBP Nommensen Pematangsiantar. Narrative writing is one of the important language skills that allows students to express imagination, personal experiences, and moral values through written communication. The study focuses on how students organize the sequence of events, develop conflicts, create tension, and use transitional signals in their narratives. The objective of this research is to identify the dominant plot patterns used by the students and to analyze how the students construct narrative elements such as exposition, rising action, climax, resolution, and reorientation. The research also examines the types of conflicts and transitional signals used in their writing. This research applies a descriptive qualitative method. The data consist of 30 narrative texts written by fourth semester students in the academic year 2024/2025. The data were analyzed through data reduction, classification, interpretation, and conclusion drawing. The findings show that most students used linear chronological plots with simple conflict development. The majority of narratives were personal experiences and fantasy stories influenced by social media trends and teenage life. The students commonly used character versus self-conflict and character versus society-conflict. In addition, the students demonstrated adequate ability in connecting events through conjunctions, adverbial phrases, and time transitions. The study concludes that vocational high school students are capable of constructing coherent narratives, although many of them still have difficulty creating complex tension and suspense